Terminal hypothermic Tau.P301L mice have increased Tau phosphorylation independently of glycogen synthase kinase 3α/β. (23rd April 2014) - Maurin, Hervé; Lechat, Benoit; Borghgraef, Peter; Devijver, Herman; Jaworski, Tomasz; Van Leuven, Fred
Abstract The microtubule‐associated protein Tau is responsible for a large group of neurodegenerative disorders, known as tauopathies, including Alzheimer's disease. Tauopathy result from augmented and/or aberrant phosphorylation of Tau. Besides aging and various genetic and epigenetic defects that remain largely unknown, an important non‐genetic agent that contributes is hypothermia, eventually caused by anesthesia. Remarkably, tauopathy in brains of hibernating mammals is not pathogenic, and, because it is fully reversible, is even considered to be neuroprotective. Here, we assessed the terminal phase of Tau.P301L mice and bigenic crosses with mice lacking glycogen synthase kinase 3 (GSK3)α completely, or GSK3β specifically in neurons. We also analysed biGT bigenic mice that co‐express Tau.P301L with GSK3β.S9A and develop severe forebrain tauopathy with age. We found that the precocious mortality of Tau.P301L mice was typified by hypothermia that aggravated Tau phosphorylation, but, surprisingly, independently of GSK3α/β. The important contribution of hypothermia at the time of death of mice with tauopathy suggests that body temperature should be included as a parameter in the analysis of pre‐clinical models, and, by extension, in patients suffering from tauopathy.